Spatiotemporal patterns of a pursuit-evasion generalist predator-prey model with prey harvesting - Guin, Lakshmi Narayan; Mondal, Benukar; Chakravarty, Santabrata (Journal of Applied Nonlinear Dynamics, 2026)
The present investigation deals with a diffusive predator-prey model in order to study the dynamic response of a reaction-diffusion model with linear prey harvesting. The governing equations of the proposed model system subject to the homogeneous Neumann boundary condition provide some qualitative interpretations of solutions to the reaction-diffusion system. The conditions of diffusion-driven instability and the Turing bifurcation region in two parameter space are explored. From the outcome of the present mathematical analysis carried out followed by the numerical simulations based on the model parameters, it reveals that for unequal diffusive coefficients, prey harvesting may induce that diffusion-driven instability resulting in stationary Turing patterns. The choice of parameter values is important to study the effect of prey harvesting and diffusion, while it depends more on the non-linearity of the model system. Moreover, the model dynamics exhibits the influence of both prey harvesting and diffusion controlled pattern formation growth to holes, stripes-holes mixture, stripes, labyrinthine, stripes-spots mixture and spots replication. All these features illustrate that the dynamics of the proposed model with the control of prey harvesting is not straightforward, but rich and complex in nature.